FAKTOR-FAKTOR YANG MEMPENGARUHI UNDERPRICING PADA PENAWARAN UMUM PERDANA DI BURSA EFEK JAKARTA - Suyatmin, Suyatmin; Sujadi, Sujadi (Universitas Muhammadiyah Surakarta, 2006)
The study aimed to examine the influence of factors in finance (firm size, ROI, financial leverage,EPS, proceeds, and current ratio) and non-finance (firmâs age, auditorâs and underwriterâs reputations,and sort of industry) on underpricing. Referring to the purposive sampling method, the number ofsamples in this study was 49 firms from 1999 to 2003. Data analysis used t test, F test, Rtest, anddouble linier regression with a 5 % level of significance. The test of financial variable influence on underpricing. The F test showed that the financialvariable influenced underpricing simultaneously. The independent variable in the model could explainthe dependent variable at 22.8%. The test of non-financial variable influence on underpricing,significant variables were the auditorâs and underwriterâs reputations, and sort of industry. The firmâsage variable influence on underpricing was insignificant. It means that the non-financial variableinfluenced underpricing simultaneously. The independent variable in the model could explain thedependent variable at 35.7%. The F test of financial and non-financial variable influences onunderpricing simultaneously.